2018
DOI: 10.1371/journal.pone.0194367
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin bio-fortified colored wheat: Nutritional and functional characterization

Abstract: Colored wheat, rich in anthocyanins, has created interest among the breeders and baking industry. This study was aimed at understanding the nutritional and product making potential of our advanced, high yielding and regionally adapted colored wheat lines. Our results indicated that our advanced colored wheat lines exhibited higher anthocyanin content and antioxidant activity than donor wheat lines and it varied in the order of white Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(90 citation statements)
references
References 27 publications
13
74
0
3
Order By: Relevance
“…They transferred genes for blue, purple and wheat pericarps from blue aleurone wheat "TA3972", purple wheat "TA3851" and black wheat to high yielding, disease resistant and locally adapted Indian wheat cultivars PBW550, PBW621 and HD2967. These developed coloured wheat lines exhibited higher anthocyanin content and antioxidant activity (black>purple>blue>white) than donor wheat lines and, high Fe and Zn content compared to amber wheat cultivars [175].…”
Section: Development Of Anthocyanin Biofortified Purple Wheatmentioning
confidence: 90%
See 1 more Smart Citation
“…They transferred genes for blue, purple and wheat pericarps from blue aleurone wheat "TA3972", purple wheat "TA3851" and black wheat to high yielding, disease resistant and locally adapted Indian wheat cultivars PBW550, PBW621 and HD2967. These developed coloured wheat lines exhibited higher anthocyanin content and antioxidant activity (black>purple>blue>white) than donor wheat lines and, high Fe and Zn content compared to amber wheat cultivars [175].…”
Section: Development Of Anthocyanin Biofortified Purple Wheatmentioning
confidence: 90%
“…Similarly, enhancement of anthocyanins content in wheat has also an important focus of wheat biofortification programs. Coloured wheat (black, blue, and purple) trait due to the high concentration of phenolics continues to be utilized in several breeding programs and varieties are already released in several nations [3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…With it, the effect of multiple pathways can be studied together. [23][24][25] In our previous study, [26] we have observed the advantage of anthocyanin-rich color wheat over white wheat biochemically as well as in the in vitro cell line studies. The present study was designed to understand the effect and underlying mechanism of anthocyanins biofortified whole colored wheat on HFD induced obesity.…”
Section: Introductionmentioning
confidence: 94%
“…Groups (iii), (iv), and (v) were fed HFD, isocaloric with group (ii), but supplemented with white, purple (total anthocyanin content (TAC) ≈ 40 ppm) and black wheat (TAC ≈ 140 ppm), respectively. [26] The experiment was conducted for 12 weeks and the body weight of the mice were measured on the weekly basis. Water and diet were provided ad libitum during the entire experiment.…”
Section: Hfd Mice Modelmentioning
confidence: 99%
“…In Uttar Pradesh, Bihar and Jharkhand, they have released high yielding (HY) zinc rich wheat BHU-3 and BHU-6 (Chitra) that can provide up to 50% of daily zinc needs [13]. Also, a research team from National Agri-Food Biotechnology Institute (NABI), India led by Monika Garg, has pushed frontiers and innovated bio-fortified black, blue and purple wheat (non-genetically modified) through crosses between HY Indian cultivars and colored wheat from Japan and America which are rich in anthocyanins (40-140 parts per million) and zinc (35-38 mg/100 g of wheat) [14]. This is a great move towards nutritional security, as these innovations in bio-fortified foods can help alleviate malnutrition only when they are scaled up with supporting policies, including augmented expenditure in agri-research and development, with due accountability to deliver.…”
Section: Green Revolution (Wheat and Rice)mentioning
confidence: 99%